Hemodynamic response after orotraqueal intubation in patients undergoing elective abdominal surgery that receive clonidine o lidocaine before anesthesia induction (Boletin Médico de Postgrado, 2020)
A single-blind controlled clinical trial was carried out with the aim to evaluate the hemodynamic response after orotracheal intubation in patients that received clonidine or lidocaine in patients undergoing elective abdominal surgery with general anesthesia at the Hospital Central Universitario Dr. Antonio María Pineda during the period May - August 2018. Fifty patients were distributed randomly and equitably in two (2) groups: group A received clonidine in a dose of 1.5 mcg/kg intravenously, 20 minutes before anesthetic induction and group B received lidocaine at a dose of 1.5 mg/kg, 90 seconds before anesthetic induction. Median age of patients was 31.6 ± 12.2 years with a predominance of female sex. Most common adverse effect was hypotension in both groups at one and three minutes post intubation; only two patients in the clonidine group showed bradycardia at three minutes. There was a statistical significant difference between both groups in regards to the mean values of systolic, diastolic and mean arterial pressure and heart rate at all time points measured after intubation.  These results confirm that clonidine is effective in reducing hemodynamic response after intubation in patients that undergo elective abdominal surgery under general anesthesia.
Keywords: hemodynamic response; orotracheal intubation; clonidine; lidocaine; abdominal surgery